Targeting FLT3 Signaling in Childhood Acute Myeloid Leukemia - Sexauer, Amy N.; Tasian, Sarah K. (Frontiers in Pediatrics, 2017)
Acute myeloid leukemia (AML) is the second most common leukemia of childhood and is associated with high rates of chemotherapy resistance and relapse. Clinical outcomes for children with AML treated with maximally intensive multi-agent chemotherapy lag far behind those of children with the more common acute lymphoblastic leukemia, demonstrating continued need for new therapeutic approaches to decrease relapse risk and improve long-term survival. Mutations in the FMS-like tyrosine kinase-3 receptor gene (FLT3) occur in approximately 25% of children and adults with AML and are associated with particularly poor prognoses. Identification and development of targeted FLT3 inhibitors represents a major precision medicine paradigm shift in the treatment of patients with AML. While further development of many first-generation FLT3 inhibitors was hampered by limited potency and significant toxicity due to effects upon other kinases, the more selective second- and third-generation FLT3 inhibitors have demonstrated excellent tolerability and remarkable efficacy in the relapsed/refractory and now de novo FLT3-mutated AML settings. While these newest and most promising inhibitors have largely been studied in the adult population, pediatric investigation of FLT3 inhibitors with chemotherapy is relatively recently ongoing or planned. Successful development of FLT3 inhibitor-based therapies will be essential to improve outcomes in children with this high-risk subtype of AML.